AVIAN INFLUENZA-H5N1 AND NEWCASTLE DISEASES IN LAYER - Nurmayani, Seli; Kencana, Gusti Ayu Yuniati; Mirah Adi, Anak Agung Ayu; Besung, I Nengah Kerta; Suratma, Nyoman Adi (Buletin Veteriner Udayana, 2023)
Avian influenza- H5N1 (AI-H5N1) and Newcastle disease (ND) are two important viral diseases in the poultry industry because they cause high economic losses. AI disease is caused by Influenza virus type A while ND disease is caused by Avian paramyxovirus type 1. AI and ND viruses are two pathogens that sometimes infect poultry together and often have similar clinical symptoms. The purpose of the examination is to determine the causative agent of the disease in order to determine a definite diagnosis. The 5-month-old Ross Brown laying hen came from a farm in Senganan Village, Penebel District, Tabanan Regency, Bali. The chicken population is 6,500 tails. Clinical symptoms of chickens include: respiratory problems, anorexia, weakness, unable to stand and green diarrhea. Chicken death occurred 5 days after the appearance of clinical symptoms. The number of sick chickens reached 1000, the chickens died more than 100, so the morbidity was 15.3%, the mortality was 1.53% and the Case Fatality Rate (CFR) was 10%. Pathological changes in anatomy include: dilation of cerebral vessels, tracheal and lung hemorrhage, edema and hemorrhage of the heart muscle, proventriculus petechial bleeding and abdominal fat, intestinal and ovarian hemorrhage and ruptured eggs were found in the abdominal cavity. Histopathological changes found congestion, hemorrhage and edema in the brain, hemorrhage and necrosis of the tracheal mucosal epithelium, multifocal hemorrhage and lung congestion, hemorrhage, edema and necrosis of the myocardium, erosion and necrosis of the intestinal villi as well as hemorrhage and regression of the ovum in the ovary. The results of virus isolation in embryonated chicken eggs resulted in the death of the embryo on the second day after inoculation which was characterized by bleeding and clear allantois fluid. The results of positive virus identification for Avian influenza-H5N1 and Newcastle diseases. Based on clinical symptoms, epidemiological data, pathological changes and HA/HI test results, it can be concluded that the case chickens were infected with Avian influenza -H5N1 and Newcastle disease viruses. Breeders are advised to carry out routine vaccinations and apply biosecurity to prevent Avian influenza-H5N1 and Newcastle disease.